2017
DOI: 10.4028/www.scientific.net/kem.740.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yttrium Addition on Microstructure and Hardness of Cast EV31A Magnesium Alloy

Abstract: The effect of the rare earth (RE) element Y on the microstructure and hardness of (Mg–0.5Zn–0.5Zr–2.8Nd –1.5Gd) wt% Mg alloy investigated. 1 wt. % Y was added and compared with the base alloy. The microstructure results show the refinement of the grain by the addition of Y and the grains became smaller about 31.8 % and the volume fraction was increases 11.1% %, which led to the increment of hardness from 48.33 HV (as-cast EV31A) to 53.71 HV (as-cast EV31A +1 Y). Energy dispersive spectroscopy (EDS) and X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The main goal was to improve the mechanical and corrosion properties by microalloying with yttrium (Y). The positive effect of Y on the microstructure and hardness of various systems of Mg-based alloys was observed [15,16]. In the case of Mg-Cu amorphous alloy, adding Y improved NaCl corrosion resistance [17].…”
Section: Introductionmentioning
confidence: 97%
“…The main goal was to improve the mechanical and corrosion properties by microalloying with yttrium (Y). The positive effect of Y on the microstructure and hardness of various systems of Mg-based alloys was observed [15,16]. In the case of Mg-Cu amorphous alloy, adding Y improved NaCl corrosion resistance [17].…”
Section: Introductionmentioning
confidence: 97%
“…ZRE1 is one of many Mg alloys available in the market nowadays. ZRE1 is an Mg alloy containing RE metal with the addition of zinc and zirconium, forming Mg-RE-Zn-Zr (Ahmad et al, 2017a). The detailed chemical composition of the ZRE1 alloy is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ZRE1 is used in the aerospace industry for intermediate casings on Tay engines, gearboxes of RB211 engines, and gearboxes of Tay engines (Materialstechnology, 2019). Research by (Ahmad et al, 2017a) explored the effect of Praseodymium (Pr) addition on the microstructure and hardness of cast ZRE1 Mg alloy. They reported that 1 wt.% Pr addition on ZRE1 cast alloy reduces the grain size of ZRE1 alloy by around 37%.…”
Section: Introductionmentioning
confidence: 99%
“…However, magnesium alloys generally show medium strength with restricted ductility at room temperature due to their hexagonal close pack structure [2]. In the recent years, magnesium alloys containing rare earth elements (RE) have received a considerately significant attention in the industry due to high mechanical strength [3] compared to the without rare earth element addition.…”
Section: Introductionmentioning
confidence: 99%
“…Solution strengthening is significantly affected by the large solubility of the heavy rare earth in magnesium at high temperature. Therefore, a lot of researches activities and developing new magnesium with heavy rare earth elements have been carried out [3,[13][14][15]. Holmium (Ho) is the one of an important element in heavy rare earth elements.…”
Section: Introductionmentioning
confidence: 99%